2016
DOI: 10.1136/neurintsurg-2016-012586
|View full text |Cite
|
Sign up to set email alerts
|

Carotid cavernous fistula after Pipeline placement: a single-center experience and review of the literature

Abstract: CCF formation is a known risk of PED treatment of CCA. Although transvenous embolization can be used for treating CCFs, parent artery sacrifice remains a viable option on the basis of these data. Studies support the view that adjunctive coiling may have a protective effect against post-PED CCF formation. None of the coiled aneurysms in our database or in the literature have ruptured. Follow-up data will lead to a better understanding of the safety profile of the PED for CCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
0
13
0
2
Order By: Relevance
“…In fact, a study by Roy et al found a CCF rate of 11.4% in their series of 44 patients who underwent the PED procedure for CCA. 63 Lin et al presented 2 such cases of direct CCFs that formed as a result of delayed aneurysm rupture following PED treatment of CCA. 43 In cases of posttraumatic and spontaneous CCF, the PED may be a possible treatment option; however, there is a lack of larger studies to confirm the results of the few reported case reports and small series presented here.…”
Section: Carotid-cavernous Fistulasmentioning
confidence: 99%
“…In fact, a study by Roy et al found a CCF rate of 11.4% in their series of 44 patients who underwent the PED procedure for CCA. 63 Lin et al presented 2 such cases of direct CCFs that formed as a result of delayed aneurysm rupture following PED treatment of CCA. 43 In cases of posttraumatic and spontaneous CCF, the PED may be a possible treatment option; however, there is a lack of larger studies to confirm the results of the few reported case reports and small series presented here.…”
Section: Carotid-cavernous Fistulasmentioning
confidence: 99%
“…Including the present case, 14 cases of dCCF due to rupture of CCA previously treated with PED deployment have been reported (Table 1); parent artery occlusion (PAO) or TVE has been performed in preceding 13 cases. [4][5][6][7][8][9][10] PAO is not recommended in such cases because it can cause cerebral ischemia even if balloon occlusion test shows ischemic tolerance. 8) Oishi et al 9) pointed out that TVE may result in sinus packing of cavernous sinus in such cases, which disturb improvement of abducens nerve palsy.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are only four reports involving 10 patients with dCCF due to a delayed aneurysm rupture after flow diverter therapy ( Table 1 ). 13 , 18 20) The flow diverters used were three Silk flow diverter stents (Balt, Extrusion, Montmorency, France) and seven PEDs. Seven patients were treated with PAO and the remaining 3 patients with transvenous coil embolization of the affected CS.…”
Section: Discussionmentioning
confidence: 99%